Pola Penanaman Karakter Mulia Terhadap Anak Didik Dalam Keluarga Berdasarkan Nilai Yang Terkandung Dalam Hadits - Muhammad Darwis Dasopang (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Education is the most important part in human life who has morals and progress. Education can be carried out by everyone in an educational institution, but the primary education should be implemented through family education which is instilled by parents towards their family members from an early age. For this paper, the author will describe the nature and understanding of education in the family; What are the hadiths about education in the family; how the methods and aspects of family education based on the hadiths. The author uses the literature review (library research), with the primary data sources from the hadiths relating to children's education in the family. Study in this paper, Islamic education requires a simultaneous process and sustainable which involves aspects of disciplinary learning and compliance to implement Islamic education towards students. Education in the family, can be found patterns that must be implemented in the family environment, for the formation of a happy family according to what was taught by the prophet Muhammad SAW, and according to the word of Allah SWT in Q.S. Lukman: 13-19